Gasification of lipid-extracted algae and fucoidan- extracted seaweeds for syngas production - Mahamud, Siti Nur Atikah (2019)
Lipid-extracted algae (LEA) are the by-products of algal lipid extraction that are used in many applications, for instance, biogas generation, ethanol manufacturing, animal feed, fertilizer, methane and as hydrogen fuel. LEA are less utilized in gasification and fucoidan-extracted seaweed residue is usually disposed after the extraction, hence, this study employed these algae residues via gasification, which is a thermochemical conversion technology of biomass into synthesis gas (syngas) to minimize the underutilization issue. The potential of lipid-extracted Nannochloropsis gaditana algae (LEA) and fucoidan-extracted algae that consist of mixture of Sargassum sp., Padina sp., and Enteromorpha sp. algae for synthesis gas production via gasification is investigated in this study. The effects of varying different process parameters; temperature and biomass loading on the synthesis gas composition, mainly H2 and CO yields are evaluated. The characterization of the samples were carried out in Fourier Transform Infra-Red (FTIR), Thermogravimetric analysis (TGA), elemental analysis and bomb calorimetry test. Kinetics study of both algae residues are carried out using Kissinger-Akahira-Sunose (KAS) and Flynn-Wall- Ozawa (FWO) models that showed the degradation behaviour of the algae residues at high temperature, as indicated by the activation energy (Ea) at different degradation (α), proximate analysis and average degradation rate (AR). The gasification experiments were performed at different process parameters; temperature (600, 700, 800, 900 and 1000 ᵒC), sample loading (0.3, 0.4, 0.5, 0.6 and 0.7 g) and equivalence ratio (ER) (0.1, 0.2, 0.3, 0.4 and 0.5) at fixed holding time (30 minutes). Yield of H2 and CO were found to increase with temperature due to the effect of oxidation, water- gas, water-gas shift and Bouduard reactions. Increasing ER value decreased H2 and CO yields due to the boosted oxidation of carbon that produced more CO2. Sample loading increment resulted in increment of H2 yield and decrement in CO yield, however, it did not significantly affect the syngas compositions, since it did not involve in the gasification mechanism. The same phenomena were observed for the data obtained from the simulation. Experimental gasification via Central Composite Design (CCD) approach revealed that optimized conditions for both samples gasification were 718.77℃, 0.3 g loading and 0.24 ER value and 766.99℃, 0.7g loading and 0.1 ER value for LEA and seaweeds residue, respectively. At this conditions, the yield of H2 and CO were 36.38 mol% and 13.28mol% respectively, for LEA and 47.99 mol% and 26.05 mol% respectively, for seaweeds residue. The experimental H2 and CO yields were largely deviated from the simulation data, as observed from the root mean square error (RMSE) values. Thus, enhancements of the experimental facilities and limitations of Aspen Plus simulation could be done to improve the RMSE values of the largely deviated data.